Sexual activity and function of adult men with spina bifida - Szymanski, Konrad M.; Roth, Joshua D.; Hensel, Devon J.; Wiener, John S.; Younsi, Nina; Stein, Raimund; Whittam, Benjamin; Kaefer, Martin; Rink, Richard C.; Cain, Mark P.; Misseri, Rosalia (Journal of pediatric urology, 2023)
Data on sexual function of men with spina bifida (SB) is limited. We aimed to assess sexual activity and erectile dysfunction (ED) in a large international sample of men with SB. Men with SB (≥18yo) were recruited in an international online survey via clinics and social media. We collected data on demographics, ambulation (Hoffer classification), penile rigidity (Erection Hardness Score), sexual activity and ED (International Index of Erectile Function). Non-parametric tests were used. A total of 162 men (median age 35, 62% shunted, 38% community ambulators) reported sexual desire similar to the general population (p = 0.82), but 55% were dissatisfied with their sex life (Summary Table). Overall, 36% reported full penile rigidity with erections, more commonly with better ambulation (p = 0.01), 69% had ever experienced orgasm and 84% ejaculated. In 44 men (27%) attempting sexual intercourse in the last 4 weeks, 59% had ED (11% severe, 7% moderate, 14% mild-moderate, 27% mild). In this group, 91% of men reporting less than full penile rigidity had ED, compared to 30% with full penile rigidity (p = 0.001). Overall, partnered non-genital contact in the last 3 months was reported by 56%, solo masturbation: 62%, partnered intercourse: 48% (31% vaginal). Of 54 men who used phosphodiesterase type 5 inhibitors (PDE5I), 80% reported improved erections, 56% improved intercourse. Overall, 40% reported non-genital erogenous zones as most pleasurable, especially with poorer ambulation (p = 0.002, chest/nipples: 73%). Strengths of this study include anonymous, voluntary, online participation maximizing participation of a heterogenous, international population. Whenever available, we compared findings to published values for the general population. Since romantic and sexual activity is a complex intersection of interest, opportunity and ability, a more comprehensive assessment was beyond the study's scope. Future work will focus on the interplay with issues like incontinence. ED was frequent among men with SB, especially in men with poorer ambulation. PDE5 inhibitors may be beneficial. Partnered sexual activity was reported by half of the men, although it may not involve penetrative intercourse.Summary TableSexual activity and function.Summary TableOutcomeNonambulators (n = 81)Household ambulators (n = 19)Community ambulators (n = 33)Normal ambulators (n = 29)p-valueOverall (n = 162)Sexual desire (median, IRQ) (IIEF items 11 and 12)7 (6–9)8 (5–9)7 (6–9)7 (6–8)0.977 (6–9)Overall sex life satisfaction, regardless of sexual activity in the last 4 weeksVery satisfied4 (4.9%)2 (10.5%)4 (12.1%)5 (17.2%)0.0615 (9.3%)Somewhat satisfied9 (11.1%)1 (5.3%)9 (27.3%)3 (10.5%)22 (13.6%)Equally satisfied and dissatisfied14 (17.3%)2 (10.5%)3 (9.1%)5 (17.2%)24 (14.8%)Somewhat dissatisfied14 (17.3%)7 (36.8%)5 (15.2%)8 (27.6%)34 (21.0%)Very dissatisfied35 (43.2%)5 (26.3%)9 (27.3%)6 (20.7%)55 (34.0%)Missing5 (6.2%)2 (10.5)3 (9.1%)2 (6.9%)12 (7.4%)Erection hardnessDoes not get bigger13 (16.1%)1 (5.3%)0 (0.0%)2 (6.9%)0.00316 (9.9%)Bigger but not hard3 (3.7%)1 (5.3%)0 (0.0%)0 (0.0%)4 (2.5%)Hard but not hard enough for penetration19 (23.5%)1 (5.3%)4 (12.1%)3 (10.3%)27 (16.7%)Hard enough for penetration but not completely hard22 (27.2%)7 (36.8%)10 (30.5%)8 (27.6%)47 (29.0%)Completely hard and fully rigid17 (21.0%)9 (47.4%)17 (51.5%)15 (51.7%)58 (35.8%)Missing7 (8.6%)0 (0.0%)2 (6.1%)1 (3.5%)10 (6.2%)Romantic and sexual activity in the past 3 monthsAny non-genital partnered contact36 (44.4%)10 (52.5)25 (75.8%)20 (69.0%)0.0191 (56.2%)Cuddled30 (37.0%)9 (47.4%)24 (72.7%)16 (55.2%)0.0179 (48.8%)Kissed33 (40.7%)8 (42.1%)24 (72.7%)16 (55.2%)0.0281 (50.0%)Held hands35 (43.2%)10 (52.6%)25 (75.8%)19 (65.5%)0.0189 (54.9%)Masturbated alone50 (61.7%)14 (73.7%)18 (54.6%)18 (62.1%)0.62100 (61.7%)Used a sex toy7 (8.6%)5 (26.3%)5 (15.2%)9 (31.0%)0.0226 (16.1%)Tested or treated for sexually transmitted infections2 (2.5%)1 (5.3%)1 (3.0%)3 (10.3%)0.257 (4.3%)Any partnered intercourse29 (35.8%)6 (31.6%)24 (72.7%)18 (62.1%)<0.00177 (47.5%)Touched partner's genitals26 (32.1%)6 (31.6%)24 (72.7%)17 (58.6%)<0.00173 (45.1%)Partner touched my genitals21 (25.9%)6 (31.6%)22 (66.7%)16 (55.2%)<0.00165 (40.1%)Gave oral sex16 (19.8%)4 (21.1%)17 (51.5%)16 (55.2%)<0.00153 (32.7%)Received oral sex16 (19.8%)5 (26.3%)13 (39.4%)15 (51.7%)0.0149 (30.3%)Vaginal sex12 (14.8%)4 (21.1%)19 (57.6%)15 (51.7%)<0.00150 (30.9%)Anal sex5 (6.2%)1 (5.3%)2 (6.1%)6 (20.7%)0.1214 (8.6%)Median age at first sexual contact (IQR)18 (16–25)18.5 (16–26)19 (18–25)20 (17–25.5)0.6319 (16–25)Full Table available in the Online Appendix.